ANALYSIS OF BRAND IMAGE AND PRICE IMPACT ON BUYING BEHAVIOR AT BU IMAS BANDUNG RESTAURANT - Frans Sudirjo; Geofakta Razali; Dian Indah Sari; I Nyoman Tri Sutaguna; Muhammad Yusuf (Universitas 45 Surabaya, 2023)
This study aims to examine how brand perception and price influence patrons' decisions at the Bu Imas Bandung restaurant. For three (three) months, from December 2022 to December 2022, this study was conducted. In this investigation, non-probability sampling was used. This survey has 95 respondents who had bought Mrs. Imas Bandung's items. The method used to collect data on brand image, pricing, and purchase decision variables was a questionnaire. The data analysis techniques used include partial hypothesis testing, or t tests, descriptive analyses, normality tests, validity tests, and reliability tests. The descriptive analysis's findings for elements influencing brand image, pricing, and purchasing behavior are in the